Unfortunately, the browser used by Answers.com for posting questions is incapable of accepting mathematical symbols. This means that we cannot see the mathematically critical parts of the question. We are, therefore unable to determine what exactly the question is about and so cannot give a proper answer to your question.

🤓

🤯

🤔

Q: What is the answer for x in 2x squared x -8 0?

Write your answer...

x squared -2x-3 equals 0 is the same as (x + 1)(x - 3) = 0

Factored?2X2 - 2X2X(X - 1)================If this were set to 0, X = 0 and X = 1

3x2 + 2x = 16 ∴ 3x2 + 2x - 16 = 0 ∴ 3x2 - 6x + 8x - 16 = 0 ∴ 3x(x - 2) + 8(x - 2) = 0 ∴ (3x + 8)(x - 2) = 0 ∴ x ∈ {-8/3, 2}

x = -1 OR x = 3

That factors to (x - 2)(x + 4) x = 2, -4

If: x2+2x-3 = 0 Then: x = 1 or x = -3

3x2-2x-8 = (3x+4)(x-2) when factored

x2 + 2x - 15 = 0(x + 5) (x - 3) = 0x = -5x = +3

2x2 + 3x - 5 = 02x2 - 2x + 5x - 5 = 02x(x - 1) + 5(x - 1) = 0(x - 1)(2x + 5) = 0x - 1 = 0 or 2x + 5 = 0x = 1 or x = -5/2

x2-2x-10-5 = 0 x2-2x-15 = 0 (x+3)(x-5) = 0 x = -3 or x = 5

No. x squared is x times x, whereas 2x is x + x.

2x^2 - 8x = -82x^2 - 8x +8 = 0, bring the -8 over to the other side2 (x^2 - 4x + 4) = 0, simplify2 (x - 2) (x - 2) = 0, factor out the equation2 = 0, x - 2 =0, x - 2 =0 , set everything egual to zero and solve for xx = 22=0 does not have an answer because it is invalid or it doesn't have a variable like the rest; 2 does not equal 0.

(2x-4)(x-1) = 0

2x to the fourth

2x2 + x - 1 = 0 2x2 + 2x - x - 1 = 0 2x(x + 1) - 1(x + 1) = 0 (2x - 1)(x + 1) = 0 So x is equal either to -1 or 1/2

x times 2x is 2x squared or 2x2

10

If: y = x^2 -2x +4 and y = 2x^2 -4x +4 Then: 2x^2 -4x +4 = x^2 -2x +4 Transposing terms: x^2 -2x = 0 Factorizing: (x-2)(x+0) => x = 2 or x = 0 Therefore by substitution points of intersect are at: (2, 4) and (0, 4)

(x + 2)(x - 4)

x2 - 2x + 55 = 90x2 - 2x - 35 = 0(x+5)(x-7) = 0x = -5, 7

5x lolzz 8)

It is: 2x squared +5x -7 = 0 and the value of x = -7/2 or 1

2x2 - 5x = 3 ∴ 2x2 - 5x - 3 = 0 ∴ 2x2 + x - 6x - 3 = 0 ∴ x(2x + 1) - 3(2x + 1) = 0 ∴ (x - 3)(2x + 1) = 0 ∴ x ∈ {-0.5, 3 }

3X = x2 - 2xsubtract 3X from each sideX2 - 5X = 0factor out an XX(X - 5) = 0=========X = 0--------orX = 5--------

-2x+16 = 0 -2x = -16 x = 8